2015
DOI: 10.1002/gps.4332
|View full text |Cite
|
Sign up to set email alerts
|

Delirium, how does it end? Mortality as an outcome in older medical inpatients

Abstract: Although the sample size precludes drawing any definite conclusion, the findings of this study suggest that delirium is not an important risk factor for subsequent mortality. Perhaps delirium and cognitive impairment share common pathophysiological pathways that are related to mortality and in which the currently used methods cannot detect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
3
0
1
Order By: Relevance
“…The only significant predictive factors for mortality were cognition as measured with the MoCA and severity of illness (APACHE-II). Regarding the association of mortality with delirium, this was not an unexpected finding as in previous work 30,31 we have found similar results. This may relate to (a) that we excluded terminally ill people, (b) we controlled for baseline cognition, and (c) issues with the small sample size.…”
Section: Discussionsupporting
confidence: 91%
“…The only significant predictive factors for mortality were cognition as measured with the MoCA and severity of illness (APACHE-II). Regarding the association of mortality with delirium, this was not an unexpected finding as in previous work 30,31 we have found similar results. This may relate to (a) that we excluded terminally ill people, (b) we controlled for baseline cognition, and (c) issues with the small sample size.…”
Section: Discussionsupporting
confidence: 91%
“…La edad avanzada es un factor constantemente asociado con delirium 2,20 , pero cuando se intenta esclarecer cómo se relacionan el delirium, la demencia y la mayor mortalidad, algunos estudios han encontrado que el delirium por sí solo es un factor independiente de riesgo de mayor mortalidad 24,25 , en tanto que otros reportan que el delirium no es un factor asociado con mayor mortalidad, como sí lo serían el deterioro cognitivo y la gravedad de la enfermedad [26][27][28][29] .…”
Section: Discussionunclassified
“…[4][5][6][7] Regardless of the risk factors leading to delirium in hospital treated elderly patients, the onset of the syndrome appears to result in increased length of hospital stay (LOS), as well as higher inhospital and early post-discharge mortality. 3,[8][9][10][11] However, several studies have found no association between delirium and hospital outcomes. 12,13 As with the rest of the world, the population of older people is increasing rapidly in Africa, with over 212 million people in the subregion projected to be 60 years or over by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…The common risk factors of delirium in older medical in‐patients include age, sensory impairment, dementia, systemic infection, metabolic and endocrine syndromes, nutritional deficiencies, cardiovascular and respiratory disorders, alcohol and drug dependence 4–7 . Regardless of the risk factors leading to delirium in hospital treated elderly patients, the onset of the syndrome appears to result in increased length of hospital stay (LOS), as well as higher in‐hospital and early post‐discharge mortality 3,8–11 . However, several studies have found no association between delirium and hospital outcomes 12,13 …”
Section: Introductionmentioning
confidence: 99%